Institutionalizing policies to attract overseas Vietnamese scientific and technological intellectuals to participate in the development of science, technology and innovation in Vietnam - Nguyen Lan Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Human resource development, including the development of scientific and technological human resources and the overseas Vietnamese experts, is one of the strategic breakthroughs confirmed in the 10-year Socio-Economic Development Strategy for 2021-2030. On May 11, 2022, the Prime Minister issued the Strategy for the Development of Science, technology and innovation until 2030, with various goals, tasks, and solutions aimed at promoting the development and application of science, technology and innovation (STI), highlighting the role and participation of the Vietnamese intellectuals abroad. With the aim to propose solutions to strengthen the attraction of overseas Vietnamese intellectuals in the development of STI, the article covers the following main topics: (i) Concept, categorization, role, and characteristics of the overseas Vietnamese intellectual community; (ii) Policies to attract and utilize overseas intellectuals in China and South Korea; (iii) The Party's and the State's policies toward overseas Vietnamese intellectuals; (iv) Proposals for institutionalizing policies to attract overseas Vietnamese scientific and technological intellectuals to participate in STI development. Code: 24102201